Thoracoscopic Esophageal Atresia with Tracheoesophageal Fistula Repair: The First Iranian Group Report, Passing the Learning Curve - Hiradfar, Mehran; Gharavifard, Mohammad; Shojaeian, Reza; Joodi, Marjan; Nazarzadeh, Reza; Sabzevari, Alireza; Yal, Nazila; Eslami, Reza; Mohammadipour, Ahmad; Azadmand, Ali (Journal of Neonatal Surgery, 2016)
Background: Thoracoscopic treatment of esophageal atresia and tracheoesophageal fistula (EA+TEF) is accepted as a superior technique at least in cosmetic point of view but it is considered as an advance endoscopic procedure that needs a learning curve to be performed perfectly. This is the first report of Iranian group pediatric surgeons in thoracoscopic approach to EA. Methods & Materials: Since 2010, twenty four cases with EA+TEF underwent thoracoscopic approach in Sarvar children Hospital (Mashhad -Iran). During the first 6 months, thoracoscopic approach to 6 cases of EA+TEF was converted to open procedure because of technical and instrumental problems. The first case of successful thoracoscopic EA repair was accomplished in 2010 and since then, 10 cases of EA+ TEF among 18 patients were treated successfully with thoracoscopic approach Results: Overall conversion rate was 58.3% but conversion rate after the primary learning curve period, was 35.7%. The main conversion causes include difficulties in esophageal anastomosis, limited exposure and deteriorating the patient’s condition. Anastomotic leak and stenosis were observed in 20% and 40% respectively. Overall mortality rate was 4.2%. Conclusion: Thoracoscopic repair of esophageal atresia seems feasible and safe with considerable superiorities to the conventional method although acceptable results needs a prolonged learning curve and advanced endoscopic surgical skill. Clear judgment about the best surgical intervention for EA according to all cosmetic and functional outcomes needs further studies.